2013
DOI: 10.1136/bmjopen-2012-002237
|View full text |Cite|
|
Sign up to set email alerts
|

Bereaved parents’ experience of stillbirth in UK hospitals: a qualitative interview study

Abstract: ObjectiveTo obtain the views of bereaved parents about their interactions with healthcare staff when their baby died just before or during labour.DesignQualitative in-depth interview study, following an earlier national survey. All interviews took place during 2011, either face-to-face or on the telephone. Data analysis was informed by the constant comparative technique from grounded theory.SettingEvery National Health Service (NHS) region in the UK was represented.ParticipantsBereaved parents who had complete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
132
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 114 publications
(158 citation statements)
references
References 36 publications
11
132
0
4
Order By: Relevance
“…The letter from the midwife that was kept by the woman as her amulet resonated with all the students and made them reflect on the role of the midwife from a personal and professional perspective. Downe et al (2013) conclude that the development of caring behaviour and empathetic engagement needs to be fostered through affective learning. Educators need to ensure that a wide range of learning strategies are used when preparing students for perinatal bereavement care.…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…The letter from the midwife that was kept by the woman as her amulet resonated with all the students and made them reflect on the role of the midwife from a personal and professional perspective. Downe et al (2013) conclude that the development of caring behaviour and empathetic engagement needs to be fostered through affective learning. Educators need to ensure that a wide range of learning strategies are used when preparing students for perinatal bereavement care.…”
Section: Discussionmentioning
confidence: 95%
“…Downe et al (2013) emphasise that everyone involved in the care of parents experiencing stillbirth has only one opportunity to do the right thing, and that parental recovery is greatly affected by the attitude and caring behaviours of staff. In a national review of support available for loss in early and late pregnancy it was found that midwifery students are generally protected from caring for women experiencing loss, and this could impact on their skills and confidence when qualified (Ottley et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations